(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Hello colleagues! I am honored to be taking on the role of Editor-in-Chief of JPOA and excited at the opportunity to follow in Dr Faiz Ali Shahs’ large footsteps as the incoming Editor-in-Chief of the Journal of Pakistan Orthopedic Association and express my gratitude at being elected for this role. Dr Faiz Ali Shah has provided expert leadership and a significant growth for the journal for more than four years now. No pressure! I shall do my best to continue the proud traditions of our POA Journal, relying on the outstanding contributions of our Editorial Team and our contributing writers. I am pleased to welcome an expert panel of associate editors and the board. I am sure they will bring immense value to our journal. As I look into the future of JPOA, the name says it all—it is the journal of the association,essentially yourJournal and mine as members of the POA. My goal is to continue thetraditions set by my predecessors andupgrade the status of JPOA. This can only be possiblewith a teamwork and sincere efforts of each individualmember of the association. Orthopedics remains a dynamic field and our journal will reflect quality research to maximise the positive effect on patient care and physician education, that high quality research and reviews bring to our profession. I promise our members that JPOA will continue to bring you quality, evidence-based reviews and research articles that affect and improve daily practice of orthopedic surgery and education. To Further hone The Skills of Writing, We Have Made A Roadmap for the Research Methodology, Article Writing Workshops for the Whole Calendar Year and I am sure it will Further the JPOA standard and help achieving the Ultimate Goal of Improving Patient Care and Surgeon S’ Education. Thank you for the opportunity to serve the POA in this role.